Soft x-ray production and spectrum measurements in imploded krypton liners - Sorokin, Sergey A.; Chaikovsky, Stanislav A. (BEAMS 2002 : 14th International Conference on High-Power Particle Beams, Albuquerque, New Mexico, 23-28 June 2002, 2002)
Experiments on efficient conversion of the pulse generator energy to soft x rays were carried out on the MIG facility (I∼1.9 MA, τ ∼80 ns). Krypton gas-puff liners were used to produce a pulse of N-shell and M-shell radiation (0.1-1 keV). A radiation yield of 50±5 kJ in ∼30 ns was attained, which made up ∼60% of the energy in the water transmission line. The x-ray power and time resolved spectrum was measured with an x-ray diode array. Both the deconvolution and edge filter techniques were used to obtain the spectra. Gas-puff filters were used to extend the spectral range of the XRD's to < 150 eV. It has been demonstrated that x-ray spectra can be adjusted by varying of the initial radius of the liner.